155k views
0 votes
The graph of this function is shifted downwards and the axis of symmetry remains x=1. Which function below the equation of the new graph select all correct answer

The graph of this function is shifted downwards and the axis of symmetry remains x-example-1
User Gringo
by
4.7k points

1 Answer

3 votes

Answer:


y=-x^(2)+2x


y=-x^(2)+2x-4


y=-x^(2)+2x-3

Explanation:

we know that

The equation of a vertical parabola in vertex form is equal to


y=a(x-h)^(2) +k

where

(h,k) is the vertex

The axis of symmetry is equal to the x-coordinate of the vertex

so


x=h

If a> 0 then the parabola open upward (vertex is a minimum)

If a< 0 then the parabola open downward (vertex is a maximum)

In this problem we have


y=-x^(2) +2x+3

The vertex is the point
(1,4) ------> observing the graph

The axis of symmetry is
x=1

If the graph of this function is shifted downwards and the axis of symmetry remains x=1

then

The x-coordinate of the vertex of the new graph must be equal to 1

The y-coordinate of the vertex of the new graph must be less than 4

The parabola of the new graph open downward

therefore

Verify each case

case a)
y=-x^(2)+2x

Convert to vertex form


y=-(x^(2)-2x)


y-1=-(x^(2)-2x+1)


y-1=-(x-1)^(2)


y=-(x-1)^(2)+1

The vertex is (1,1)

therefore

The function could be the equation of the new graph

case b)
y=-x^(2)-2x+3

Convert to vertex form


y-3=-(x^(2)+2x)


y-3-1=-(x^(2)+2x+1)


y-4=-(x+1)^(2)


y=-(x+1)^(2)+4

The vertex is (-1,4)

therefore

The function cannot be the equation of the new graph

case c)
y=-x^(2)+2x-4

Convert to vertex form


y+4=-(x^(2)-2x)


y+4-1=-(x^(2)-2x+1)


y+3=-(x-1)^(2)


y=-(x-1)^(2)-3

The vertex is (1,-3)

therefore

The function could be the equation of the new graph

case d)
y=-x^(2)+2x+4

Convert to vertex form


y-4=-(x^(2)-2x)


y-4-1=-(x^(2)-2x+1)


y-5=-(x-1)^(2)


y=-(x-1)^(2)+5

The vertex is (1,5)

therefore

The function cannot be the equation of the new graph

case e)
y=-x^(2)+2x-3

Convert to vertex form


y+3=-(x^(2)-2x)


y+3-1=-(x^(2)-2x+1)


y+2=-(x-1)^(2)


y=-(x-1)^(2)-2

The vertex is (1,-2)

therefore

The function could be the equation of the new graph

User Andrey Vlasovskikh
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.